Cortisol stress response after musculoskeletal surgery: a narrative review : general orthopaedics - Menger, Maximilian M.; Histing, Tina; Laschke, Matthias W.; Ehnert, Sabrina; Viergutz, Tim; Fontana, Johann (EFORT open reviews, 2025)
Trauma induced by surgery stimulates a neuroendocrine stress response, substantially increasing cortisol levels in the post-surgical setting. This has substantial effects on metabolism, water and electrolyte balance as well as on the cardiovascular, nervous and immune systems. While there are valid data on cortisol level courses in a variety of specific pathologies, such as septic shock, acute respiratory distress syndrome, bacterial meningitis, cardiac arrest, community-acquired pneumonia and influenza, there is a persisting lack of data on the cortisol stress response after musculoskeletal surgery. The present review provides an overview of the current state of research regarding trauma-induced cortisol response after musculoskeletal interventions, including both elective orthopedic surgery and trauma surgery. Trauma induced by musculoskeletal surgery triggers a cortisol response, which varies significantly depending on the type of surgery and its invasiveness. Notably, elective orthopedic procedures demonstrate a smaller range of cortisol levels compared to musculoskeletal trauma and surgery. In the future, high-quality prospective trials need to analyze the factors that may modulate the adequate adrenal response to stress, such as preoperative long-term treatments with glucocorticoids, as well as the potential impact of low cortisol levels and perioperative cortisol substitution therapy on pain management, blood requirements, catecholamine dependency, delirium and mortality after musculoskeletal surgery.
Gesehen am 23.06.2025